Ultrasonographic and endocrine aspects of follicle deviation, and acquisition of ovulatory capacity in buffalo (Bubalus bubalis) heifers - Gimenes, L. U.; Carvalho, N. A. T.; Sa Filho, M. F.; Vannucci, F. S.; Torres-Junior, J. R. S.; Ayres, H.; Ferreira, R. M.; Trinca, L. A. [UNESP]; Sartorelli, E. S. [UNESP]; Barros, C. M. [UNESP]; Beltran, M. P. [UNESP]; Nogueira, Guilherme de Paula [UNESP]; et al. (Elsevier B.V., 2011)
The objectives of this study were to determine the interval from ovulation to deviation and the diameter of the dominant (DF) and largest subordinate (SF) follicles at deviation in buffalo (Bubalus bubalis) heifers. Two methods of evaluation (observed vs. calculated) were used. FSH and LH profiles encompassing follicle deviation (Experiment 1), and the follicular diameter when the DF acquired ovulatory capacity (Experiment 2) were also determined. The time of deviation and the diameter of the of and the largest SF at deviation did not differ between observed and calculated methods. Overall, follicle deviation occurred 2.6 +/- 0.2 d (mean SEM) after ovulation, and the diameters of the DF and SF at deviation were 7.2 +/- 0.2 and 6.4 +/- 0.2 mm, respectively. No changes in plasma levels of FSH or LH were observed (P= 0.32 and P= 0.96, respectively). Experiment 2 was conducted in two phases according to the diameter of the of during the first wave of follicular development at the time of LH challenge (25 mg of pLH). In the first phase, follicles ranging from 5.0 to 6.0 mm (n = 7), 6.1 to 7.0 mm (n = 11), or 7.1 to 8.0 mm (n= 9) were used, and in the second phase, follicles ranging from 7.0 to 8.4 mm (n=10), 8.5 to 10.0 mm (n = 10), or 10.1 to 12.0 mm (n = 9) of diameter were used. After the pLH treatment, the of was monitored by ultrasonography every 12 h for 48 h. No ovulations occurred in heifers in the first phase. However, in the second phase, an effect of follicular diameter was observed on ovulation rate [7.0-8.4 mm (0.0%, 0/10), 8.5-10.0 mm (50.0%, 5/10), and 10.0-12.0 mm (55.6%, 5/9)]. In summary, follicle deviation occurred 2.6d after ovulation in buffalo (B. bubalis) heifers, when the diameters of the DF and SF were 7.2 and 6.4 mm, respectively. No significant changes in plasma concentrations of FSH or LH were detected. Finally, the acquisition of ovulatory capacity occurred when the of reached 8.5 mm in diameter. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Buffaloes; Follicle deviation; Follicle selection; FSH; LH; Ovulation capacity